Pendidikan Agama Islam dan Peningkatan Keterampilan Sosial dalam Memainkan Peran Penting Membentuk Karakter Moral dan Sosial Siswa - Siti Nurhaliza (Integrated Education Journal, 2024)
This study aims to examine the enhancement of social skills through Islamic Religious Education (PAI). Islamic Religious Education plays a crucial role in shaping students' moral and social character. The enhancement of social skills such as communication, cooperation, tolerance, and empathy among students is central to this study. The approach used in this research includes qualitative methods based on library research. The data collection technique involves gathering secondary data from various sources such as books, journals, and previous research. The findings indicate that Islamic Religious Education, when presented with an interactive and contextual approach, can significantly improve students' social skills. For example, group discussions in Islamic Religious Education classes encourage students to be more open and respectful of others' opinions, while community service activities instill values of empathy and care for others. These findings affirm that integrating Islamic values into daily educational practices can strengthen social bonds and prepare students to become more adaptive individuals who contribute positively to society. The conclusion of this research is that Islamic Religious Education not only serves as a means of religious instruction but also as an effective instrument in the development of essential social skills for community life